L’hypermédia Au Service De La Formation Initiale D’enseignants-Stagiaires (Cas Du CRMEF-FESMEKNES) - Youssef Nafidi; Anouar Alami; Moncef Zaki; Hanane Afkar; Mohammed Elazami Elhassani (European Scientific Journal, ESJ, 2017)
In light of empirical experience from Morocco, combined with new possibilities afforded by Information and Communication Technology (ICT), there is a wish to integrate new technologies into distance education to help solve a set of problems identified in the initial training at the Regional Centre for the Professions of Education and Training of Fez-Meknes. The results of a study conducted among 15 trainee teachers of the Earth and Life Sciences allow us to conclude that designing a hypermedia tool for learning could constitute a promising solution to address the many challenges linked to the initial training of teachers in Morocco. Finally, the use of this digital resource by trainee teachers’ has also strongly contributed to their eagerness to integrate ICT in their subsequent teaching practices.